A Bulk-Driven ISFET-Based Chemical Mixer - Zain,WSW; Prodromakis,T; Toumazou,C (IEEE, 2010)
In this work the concept of the chemical mixerfor comparing the pH of two aqueous solutions is introduced. Ionic concentrations are sensed via a pair of ISFETs, which are then translated into signals with frequencies that correspond to the pH values of the solutions. Using the bulk-driven single balanced topology, the number of transistors is significantly reduced, making it suitable for applications where a low supply voltage and low power consumption are essential. Finally, it is demonstrated that the output frequency of the mixer depends on the ΔpH of the solutions under test.